Low Gain Avalanche Detector development for the LHC’s High-Luminosity Upgrade at Teledyne e2v - Allport, P; Bortoletto, D; Gazi, M; Gonella, L; Hynds, D; Jordan, D; Kopsalis, I; McMahon, S; Mulvey, J; Plackett, R; Stefanov, K; Villani, EG (Elsevier, 2022)
The need for ultra-fast timing is a result of the expected pile-up at the High-Luminosity LHC General-Purpose Detectors. Track timing resolution of the order of tens of picoseconds is required to sufficiently resolve individual vertices. In collaboration with Teledyne e2v, 22 six-inch wafers with Low Gain Avalanche Detectors, featuring a 50 μm thick high-resistivity epitaxial layer and different gain layer implants, have been completed successfully. Using transient current technique, the charge gain of a 1 × 1 mm 2 LGAD device from one of the wafers was found to be higher than 10, with jitter reaching 10 ps when biased at 240 V. Tests with other wafers are under way.